2018
DOI: 10.1177/2472555218786210
|View full text |Cite
|
Sign up to set email alerts
|

Is Targeting the Inflammasome a Way Forward for Neuroscience Drug Discovery?

Abstract: Neuroinflammation is becoming increasingly recognized as a critical factor in the pathology of both acute and chronic neurological conditions. Inflammasomes such as the one formed by NACHT, LRR, and PYD domains containing protein 3 (NLRP3) are key regulators of inflammation due to their ability to induce the processing and secretion of interleukin 1β (IL-1β). IL-1β has previously been identified as a potential therapeutic target in a variety of conditions due to its ability to promote neuronal damage under con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 316 publications
(501 reference statements)
0
13
0
2
Order By: Relevance
“…However, it is important to determine whether the same mechanisms occur in cells that may experience tissue-specific disease conditions. Recent research has demonstrated that microglia form inflammasomes during Alzheimer's disease (19), and inflammasomes are implicated in the progression of a number of other neurological and neurodegenerative conditions (20). Thus, we investigated the relationship between IL-1β release and membrane permeability and cell death in cultures of glial cells (astrocytes and microglia) isolated from the brains of mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to determine whether the same mechanisms occur in cells that may experience tissue-specific disease conditions. Recent research has demonstrated that microglia form inflammasomes during Alzheimer's disease (19), and inflammasomes are implicated in the progression of a number of other neurological and neurodegenerative conditions (20). Thus, we investigated the relationship between IL-1β release and membrane permeability and cell death in cultures of glial cells (astrocytes and microglia) isolated from the brains of mice.…”
Section: Resultsmentioning
confidence: 99%
“…All animal procedures were performed with appropriate personal and project licenses in place, in accordance with the Home Office (Animals) Scientific Procedures Act (1986) and approved by the Home Office and the local Animal Ethical Review Group, University of Manchester. As described previously (20), brain tissue was mechanically digested, and cells were maintained in DMEM, 10% FBS, PenStrep until 80% confluence was reached (10–13 days in vitro ). Cultures were then reseeded at a density of 1.7 × 10 5 cells/ml.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, in addition to ischemia/reperfusion diseases, inflammasomes have been implicated in the pathogenesis of many other diseases, including neurodegenerative diseases. Thus, development of small molecules that target different inflammasomes, but primarily NLRP3 inflammasome, has attracted considerable attention over the past decades [ 10 , 33 ]. MCC950 is regarded as the most specific NLRP3 inhibitor to date, as it does not inhibit the NLRP1, NLRC4, and AIM2 inflammasomes [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…This class of compounds inhibits ATP‐ and nigericin‐mediated activation of the NLRP3 inflammasome (Daniels et al, ). This mechanism of action is independent of COX enzyme inhibition and seems to involve inhibition of the volume‐regulated anion channels (Swanton et al, ). Mefenamic acid and flufenamic acid have weak potency but are specific for NLRP3 over other inflammasomes.…”
Section: Nlrp3 Inflammasomementioning
confidence: 99%